D dimer as Biomarker for Covid-19 severity - Parveen Shaikh, Nameera; Parveen Shaikh, Aleena; Murvanidze, Ia; Saralidze, Eteri; Nakashidze, Irina (The Ukrainian Scientific Medical Youth Journal, 2023)
Coronavirus infectious disease 2019 (COVID-19) infections, a highly coagulative and inflammatory state, predispose patients to arterial and venous thrombotic events due to platelet activation, endothelial dysfunction, and stasis.  There are several reasons why elevated levels of D-dimer indicate the severity of the disease.  This review paper aims to revise the significance of D-dimer levels in the covid-19. Thus, according to the studies, the increase in D-dimer level was significantly associated with the severity of the disease's course and the mortality rate.   Moreover, in the case of mortality of hospitalized patients, a very high level of D-dimer is detected, which confirms that D-dimer can be used as a valuable biomarker for evaluating clinical outcomes in patients with Covid-19.